Individuality of responses to bilateral and unilateral volume equated hypertrophic strength training in physically active men - Räntilä, Aapo (2019)
Purpose. The purpose of the present study was to investigate possible differences between unilateral and bilateral strength training during ten weeks progressive hypertrophic strength training and six weeks detraining period. Furthermore, it was examined possible different individual responders in muscle hypertrophy during strength training and, how those different responders would behave during the detraining phase following the training period.